Conflict management and its diagnostics in social structure relationship networks - Rachwał, Aleksandra (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Society’s historical security depends on its management of a mix of the economy’s most important risk factors. These risk factors include the following sectors: health, banking, enterprises, insurance system, pension funds, social networks, media, space management and regulative sectors. In the culture of the functional imperative which is focused on maximising the profit of enterprises, class and social structure can constitute either a firewall or open the doors to the performance of cultural obligations in the society. If social structures are poorly integrated, the maintaining of their stability and the stability of social order is put in danger. According to the World Health Organization, average life expectancy in the period between the years 1999 and 2000 was 61.4 years, while forecasts for the years 2020-2025 expect its increase to 71.6 years. It is anticipated that the entire population of developed countries will increase by 94% whilst the population of people that are 60 years or older will increase by 240%. This of course, definitely means that there will be a significant shift in age proportions toward the growth of the elderly population (Walden-Gałuszko de 2008: 3) and it constitutes a crucial argument in the societal discussion concerning health, disease, and long-term health care standards. Problems related to health-treatment, long waiting times for an appointment with the doctor, difficulties concerning accessing distant specialised health centres (clinics), existing information deficit on where and how to look for all kinds of support, paralysing stress, periodical lack of life-saving drugs, non-caring inhumane regulations, the loss of income in the family – all of the above-listed are just some of the problems faced by families taking care of family member who are suffering from cancer. Society’s major task as far as the development of palliative care is concerned is not only the permanent acquisition of families to perform care for the cancer-stricken patients but also investing in perfecting the caregivers’ skills that are vital especially in consequences arising after oncological treatment, such skills include those needed in combating pain, and skills necessary for palliative care. The main point of society’s departure from the reductionist biomedical model towards the epidemiological model results in a significant reduction in mortality due to chronic diseases (such as cardiovascular disease, stroke, diabetes and cancer). Nowadays this has led to an increase in the population of people living day by day with chronic disease, and consequently has led to an increase in demand for long-term care and long-term community support. One of the major challenges faced by medical science was the development of new evaluation parameters used for assessing the efficiency of medical care. Parameters include more than objective indicators of care (such as percentage decrease in mortality). Another challenge involves moving towards inclusion of the patient’s perspective on the care provided (patient-centered outcomes) (Tobiasz-Adamczyk 2002: 41). When economic transition accelerates, the rebuilding of social organisation and social consciousness does not keep pace with the speed of the changes. In such conditions people that are left to themselves, no longer know what is possible and what is impossible, what is fair and what is unfair; what hopes and revindications they are entitled to, and those in which they are going too far (Szacki 2006: 392). In this situation, necessary measures on behalf of the state must be taken to foster a family capable of taking care of the ill. It is very important to protect the healthy family which incidentally happens to be in a situation of crisis due to a family member’s grave illness. There is a strong need to support the family in the implementation of tasks related to their caring function and tasks related to meeting the basic needs of the ill family member. Family must be perceived from a broader perspective. We must examine it, as at a healthy family which incidentally, due to family member’s sickness, happens to be in a crisis situation. With the introduction of a social support strategy for the family as a unit of care, a possible reduction in the number of hospitalisations may take place and there also may be an increase in the independence and autonomy of the families. There will be an increase in a family’s ability to resolve everyday problems, to rebuild the necessary social support networks, and to improve the quality of care for sick members of the family.
Keywords: family; hospitalization; social support; relationship